Fundamental Modes of Swimming Correspond to Fundamental Modes of Shape: Engineering I‐, U‐, and S‐Shaped Swimmers. (28th July 2021) - Sharan, Priyanka; Maslen, Charlie; Altunkeyik, Berk; Rehor, Ivan; Simmchen, Juliane; Montenegro-Johnson, Thomas D.
Abstract : Hydrogels have received increased attention due to their biocompatible material properties, adjustable porosity, ease of functionalization, tuneable shape, and Young's moduli. Initial work has recognized the potential that conferring out‐of‐equilibrium properties to these on the microscale holds and envisions a broad range of biomedical applications. Herein, a simple strategy to integrate multiple swimming modes into catalase‐propelled hydrogel bodies, produced via stop‐flow lithography (SFL), is presented and the different dynamics that result from bubble expulsion are studied. It is found that for "Saturn" filaments, with active poles and an inert midpiece, the fundamental swimming modes correspond to the first three fundamental shape modes that can be obtained by buckling elastic filaments, namely, I, U, and S‐shapes. Abstract : Enzyme‐driven micromotors show different motion modes, depending on their shape: the zeroth shape mode (I) typically results in pumping, the first one (one bend, U) in translation, and the second one (two bends, S) in rotation.